2016
DOI: 10.1093/humrep/dew120
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled, non-inferiority trial of modified natural versus artificial cycle for cryo-thawed embryo transfer

Abstract: 20 April 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
114
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 32 publications
7
114
0
2
Order By: Relevance
“…Of the six studies included, there is one powerful, multi-center RCT (ANTARCTICA trial) reporting comparable live birth rates [50]. However, significantly more cycles had been cancelled in the AC without suppression group (124/464 versus 101/495, OR 1.4, 95 % CI 1.1-1.9, p = 0.02).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the six studies included, there is one powerful, multi-center RCT (ANTARCTICA trial) reporting comparable live birth rates [50]. However, significantly more cycles had been cancelled in the AC without suppression group (124/464 versus 101/495, OR 1.4, 95 % CI 1.1-1.9, p = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, no LPS was employed in the mNC arm [36,50]. Without LPS, there was no significant difference for clinical pregnancy (OR 1.08, 95 % CI 0.88-1.33; two studies) or live birth rates (OR 1.23 95 % CI 0.98-1.55; two studies).…”
Section: Tnc Versus Ac With Suppressionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a randomized multicenter clinical trial, Groenewoud et al in 2012 detected that there is no significant difference in live birth rates between natural and artificial methods (11). In another study in 2016, modified natural withthe artificial cycle for cryo-thawed embryo transferwere compared and it was observed observed that there is no significant differences in live birth rate (11.5% vs. 8.8%) and clinical pregnancy rate (19% vs. 16.0%) between two groups of modified NC-FET and AC-FET(12). A recent meta-analysis by Yarali et al shows that at the moment there is not sufficient evidence to support the use of any protocols (13).…”
Section: Discussionmentioning
confidence: 99%
“…Following treatment with exogenous ovarian steroids after pituitary desensitization, we expected conditions in the endometrium approximating those in the normal menstrual cycle, as it happens in an artificial endometrium developed by these steroids for transfer of cryopreserved embryos, which in terms of the clinical outcome is not inferior to an endometrium in a modified natural cycle [34]. In the present study, a group of normally cycling women was not included; however, the hormonal profile in the simulated cycles in terms of E2 and PRG changes resembled that in a spontaneous cycle and did not differ significantly between the metformin group and the control group.…”
Section: Discussionmentioning
confidence: 99%